Letter - Urrutia, Manuel
1939-03-07 025a-0142-001 Codes used { Bentleys Complete & 2nd phrase A.B.C. 6th & 7th Ed. Boe (New Edition) and Acme Telegrams { Inland: Midatlan Stock London Foreign: Midatlan London Telephone: Mansion House 2164-8 (5 lines) Mid-Atlantic Shipping Company Limited. Directors M. Gamboa U.S.A. J.I. Aldama Spanish E.L Burbidge British Creechurch House Bevis Marks London E.C.3. Your Ref. Our Ref. DA/GV 7th March, 1939. Mr. H. V. Tewson Asst. Gen. Secretary Transport House, Smith Square, S. W. 1 Dear Sir, We refer to our conversation of to-day and now have pleasure in enclosing herewith list and two copies of the ships, ports, captains and crews of same. Thanking you for your attention, We remain, Yours faithfully Manuel Urrutia. Marcelino González. 292/946/25a/142(i)